Neukeynesianismus und Postkeynesianismus: Was für ein Unterschied! - Walterskirchen, Ewald (Wirtschaft und Gesellschaft, 2016)
There are fundamental differences between Neokeynesianism and Postkeynesianism. First of all, Neokeynesianism is today, besides New Classical Macroeconomics, one of the two strands of the mainstream („Saltwater and Freshwater economics“). Postkeynesianism, on the other hand, is a heterodox economic school. By and large, Neokeynesians are liberals, and Postkeynesians are left Keynesians. The New Keynesians are, on the whole, neoclassical economists who are in favour of anti-cyclical Keynesian policy measures. They stick to the neoclassical assumption that the economy tends towards full employment. In the long run, prices and wages are flexible enough to restore full employment. In the short run, however, prices and wages are sticky for rational micreconomic reasons. Due to this stickiness, interventions of central banks are inevitable. The Postkeynesians reject the neoclassical idea of full-employment equilibrium. Underutilisation of capital and labour is the normal state. Downward-flexibility of wages and prices would not restore full employment, but result in deflation. Effective demand – not potential supply – is crucial for the long-run development of output and employment. Since financial markets are inherently instable, they must be strictly regulated.